Numerical investigation of isolated filament motion in a realistic tokamak geometry. (5th October 2015) - Walkden, N.R.; Dudson, B.D.; Easy, L.; Fishpool, G.; Omotani, J.T.
Abstract: This paper presents a numerical investigation of isolated filament dynamics in a simulation geometry representative of the scrape-off layer (SOL) of the Mega Amp Spherical Tokamak (MAST) previously studied in Walkden et al 2013 ( Plasma Phys. Control. Fusion 55 105005). This paper focuses on the evolution of filament cross-sections at the outboard midplane and investigates the scaling of the centre of mass velocity of the filament cross-section with filament width and electron temperature. By decoupling the vorticity equation into even and odd parity components about the centre of the filament in the bi-normal direction parallel density gradients are shown to drive large velocities in the bi-normal (approximately poloidal) direction which scale linearly with electron temperature. In this respect increasing the electron temperature causes a departure of the filament dynamics from two-dimensional (2D) behaviours. Despite the strong impact of three-dimensional effects the radial motion of the filament is shown to be relatively well predicted by 2D scalings. The radial velocity is found to scale positively with both electron temperature and cross-sectional width, suggesting an inertially limited nature. Comparison with the two-region model (Myra et al 2006 Phys. Plasmas 13 112502) achieves reasonable agreement when using a corrected parallel connection length due to the neglect of diamagnetic currents driven in the divertor region of the filament. Analysis of the transport of particles due to the motion of the filament shows that the background temperature has a weak overall effect on the radial particle flux whilst the filament width has a strong effect.